Instrumentos y prácticas de enseñanza de las ciencias físicas y químicas en la Universidad de Valencia, durante el siglo XIX - Simó Castell, Josep; García Belmar, Antonio; Bertomeu Sánchez, José Ramón (ENDOXA, 2005)
This study is an attempt to reconstruct the evolution of spaces and scientific equipments used for the teaching of physics and chemistry in the University of Valencia in the 19th century. Through an analysis of the instruments' characteristics and their spatial distribution, the teaching programs and textbooks, as well as the profile of the target pubhc, we try in this essay to understand the evolution of the didactic methods employed by the successive teachers and assistants when teaching physics and chemistry in the existing cabinets, amphitheatres and laboratories.